Figurative language and imagery in Hindia's song lyrics on the album “Lagipula Hidup Akan Berakhir” - Retno Oktafiayu Ariesya; Rustono Rustono (Universitas Muhammadiyah Malang, 2026)
This study examines the use of figurative language and imagery in the song lyrics of Hindia’s album Lagipula Hidup Akan Berakhir through a stylistic approach. While previous studies on song lyrics tend to focus on isolated texts, they rarely explore how stylistic patterns operate systematically across a complete album as a unified textual entity. This study aims to identify types of figurative language, classify forms of imagery, and explain their stylistic functions in constructing existential meanings within the album. This research employed a qualitative descriptive design. The data consist of words, phrases, clauses, and sentences containing figurative language and imagery drawn from all songs in the album. Data were collected using listening and note-taking techniques and analyzed through an interactive model involving data reduction, data display, and conclusion drawing. A coding framework was used to systematically categorize figurative devices and imagery types. The findings reveal that comparative figures of speech, particularly metaphor, simile, and personification, are the most dominant forms. These expressions function as conceptual tools to represent abstract experiences such as loss, anxiety, and mortality. Oppositional figures, including irony, paradox, and hyperbole, help convey emotional tension and social critique. In terms of imagery, visual imagery is the most dominant type, indicating a strong reliance on visual representation to construct meaning and enhance imaginative engagement. This study contributes to stylistic studies by demonstrating that song lyrics within a single album exhibit consistent, systematic stylistic patterns that function cohesively to construct existential themes.